KARAKTERISTIK PERMUKIMAN KUMUH DI KELURAHAN PAYU PUTAT PRABUMULIH - Ricky Ravsyan Alhafez (Jurnal Tekno Global, 2016)
Economic factors and the increasing number of residents resulted in the availability of land decreases. Communities with middle and upper economic level course will easily find suitable land allotment for a place to stay. While inversely proportional to the lower middle income people who can hardly be said of land - the land they occupy is certainly not in conformity with the allotment of land as a place for living. And usually with a low economic level of the occupancy of the community are far from habitable. Can hardly be said that all parts of Indonesia there are slums, and not least in the area of Breast Putat village Prabumulih. The area is located in the banks of the river should be a green open spaces are just a lot of settlements - settlements that are not habitable building with major construction timber and do not care about good sanitation as if - if mushroomed in the region. See the facts on the ground which does not allow for the relocation of people living in the area at this time to be a challenge to help both the community and the government to give an idea as to what the character of the existing settlements in the Region's Breast Putat. So that could be considered for the government to relocate or improve existing settlements. Keywords: Economic factors, slums, Payu Putat Prabumulih Village